Implementasi Visi Fo Guang Shan dalam Pengembangan Bakat Umat Buddha: Studi Pendidikan Dharma, Pelestarian Budaya, dan Praktik Spiritual di Lingkungan Multikultural - Marshella Marshella; Widodo, Urip; Yatno, Tri (Jurnal Budi Pekerti Agama Buddha, 2026)
This study analyzes the implementation of the Fo Guang Shan vision in developing the talents of Buddhist followers through Dharma education, cultural preservation, and spiritual practice within a multicultural environment. In the context of globalization, Buddhist communities face challenges in maintaining spiritual identity while adapting to diverse social and cultural settings. This research aims to examine how Humanistic Buddhism is applied in talent development programs and to evaluate its relevance in multicultural contexts. The study employs a qualitative descriptive approach with a case study design. Data were collected through participatory observation, documentation, reflective notes, and literature review. The findings indicate that the integration of Dharma education, cultural activities, social service, and spiritual practices forms a holistic development model that balances intellectual growth, character formation, emotional maturity, and social responsibility. The implementation demonstrates that talent development is not limited to technical skills but also emphasizes ethical values and spiritual awareness. This model offers a contextual and inclusive framework that can contribute to sustainable Buddhist community development in the era of globalization.